MEWUJUDKAN KETAHANAN SOSIAL MASYARAKAT MELALUI PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) DI DESA EKANG ANCULAI KABUPATEN BINTAN - Afrizal, Afrizal; Handrisal, Handrisal (UIR PRESS, 2019)
One of the objectives of the existence of Badan Usaha Milik Desa (BUMDes) is to improve the welfare of village communities. This will be realized if the community has economic, educational and social resilience. This research wants to see how the existence of BUMDes, especially in the village of Ekang Anculai, which has been running well, is able to contribute to the community in the aspect of social resilience. The results of the study state that although it is not significant, the existence of BUMDes is able to change the mindset of the community in improving the standard of living, especially in the economic aspect by starting from growing individual resilience which ultimately impacts on community resilience in creating a better community environment. Some of the obstacles faced in realizing social resilience are that there are still few people who are positively affected by the existence of BUMDes to create communities that have social resilience.